(3cJGH LejY eG aj GdbQBf GdcQje ef GdBjGJ GdcQjeI GdfGSNI hGdefShNIs - (3GdeXaQ Hf GdMSjf Hf RjO Hf Ydj MPjeI GdaGQSjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf hHYO agPG GdcJGH LeYJ ajg LejY eG ai GdbQBf ef GdBjGJ GdfGSNI hGdefShNI HGH HjGf GdfGSN hGdefShN s
(3BNQgG (B:s
(3hef GdfGSN ehVY GdgeRI Edi BNQ GdbQBf eMceGJ GdCbd jG CjgG GdcGaQhf aEf ajgG ef GdefShN ehVY hdG fGSN ajgG Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs